Sperm cellular and nuclear dynamics associated with ram fertility - Bodu, Mustafa; Hitit, Mustafa; Sari, Ayse; Kirbas, Mesut; Bulbul, Bulent; Ataman, Mehmet Bozkurt; Bucak, Mustafa Numan; Parrish, John; Kaya, Abdullah; Memili, Erdogan (Frontiers in Veterinary Science, 2025)
The aim of this study is to analyze DNA integrity, shape morphology, and membrane integrity in sperm from low-fertility (LF) and adequate- or normal-fertility (AF) rams. Various sperm evaluation methods such as sperm chromatin dispersion assay, Fourier harmonic amplitude (FHA) analysis, and other image analysis of morphometric parameters were used. An additional aim is to employ new statistical models with high reliability to predict ram fertility based on sperm head morphology parameters. Fresh semen was collected from 41 AF (conception rate 95.1% ± 0.6%) and 27 LF (conception rate 79.7% ± 2.5%) rams using artificial vagina. Differences (p < 0.05) were observed in percent motile sperm (mean ± SEM, 64% ± 3%, 72% ± 2%), percent viable sperm (78 ± 2%, 84 ± 1%), and head and acrosome abnormalities (1.9% ± 0.4%, 3.4% ± 0.4%) between LF and AF rams. The findings of different analyses also showed that the fertility of rams is not associated with DNA fragmentation (p > 0.05). Using the FHA analysis, an average head shape of ram sperm was constructed and harmonic amplitude 2 was determined, which tended to differ between the two ram fertility groups (p = 0.059). Based on the FHA and morphometric analysis, a significant linear discriminant model was constructed (p = 0.0013), which allowed for specificity in identifying LF rams (6/9, 66.7%) and sensitivity in identifying AF rams (39/47, 83.0%). The overall error rate remained good, which was 11/56 (20%). The findings of this study suggest that sperm DNA damage might not be used to predict ram fertility and that the statistical model based on the FHA analysis can be a potential tool in predicting ram fertility.